Population genetics and ecological niche of invasive Aedes albopictus in Mexico - Pech May, Angélica del Rosario (2016)
The Asian tiger mosquito Aedes albopictus (Skuse), is one of the most invasive mosquito species worldwide. In Mexico it is now recorded in 12 states and represents a serious public health problem, given the recent introduction of Chikungunya on the southern border. The aim of this study was to analyze the population genetics of A. albopictus from all major recorded foci, and model its ecological niche. Niche similarity with that from its autochthonous distribution in Asia and other invaded countries were analyzed and its potential future expansion and potential human exposure in climate change scenarios measured. We analyzed 125 sequences of a 317. bp fragment of the cyt b gene from seven A. albopictus populations across Mexico. The samples belong to 25 haplotypes with moderate population structuring (Fst. = 0.081, p<. 0.02) and population expansion. The most prevalent haplotype, found in all principal sites, was shared with the USA, Brazil, France, Madagascar, and Reunion Island. The ecological niche model using Mexican occurrence records covers 79.7% of the country, and has an 83% overlap with the Asian niche projected to Mexico. Both Neotropical and Nearctic regions are included in the Mexican niche model. Currently in Mexico, 38.6 million inhabitants are exposed to A. albopictus, which is expected to increase to 45.6 million by 2070. Genetic evidence supports collection information that A. albopictus was introduced to Mexico principally by land from the USA and Central and South America. Prevalent haplotypes from Mexico are shared with most invasive regions across the world, just as there was high niche similarity with both natural and invaded regions. The important overlap with the Asian niche model suggests a high potential for the species to disperse to sylvatic regions in Mexico.